ASSESSING RETAIL TRADE EFFICIENCY BASED ON STATISTICAL INDICATORS - Gaybullayev , Sarvar (Scientific practical conference, 2026)
This study investigates the assessment of efficiency in the retail trade sector using statistical indicators. The research develops a comprehensive framework that integrates key performance measures such as sales turnover, profitability, cost efficiency, labor productivity, and inventory turnover. Using quantitative methods, including descriptive statistics, correlation analysis, and regression approaches, the study identifies the main determinants of retail efficiency.The findings suggest that retail performance is a multidimensional phenomenon influenced by both internal management practices and external market conditions. The study contributes to the literature by providing a structured statistical approach to efficiency evaluation and offers practical recommendations for improving retail performance through data-driven decision-making.